SISTEM INFORMASI PEMBELIAN DAN PENGELUARAN KAS PADA CV.ANGKASA BARU - Siswanto Siswanto; Maya Utami Dewi; Lutfi Anggraini; Agustinus Budi Santoso (Universitas Sains dan Teknologi Komputer, 2020)
The information system for purchases and cash disbursements is one of the entire information systems. In retail sales companies need control of purchases and cash disbursements that are precise and fast. In an effort to minimize sudden out-of-stock inventory, it is necessary to secure an inventory to cope with a sudden out of stock due to delays in purchasing goods that occur at CV. New Space. This is what encourages the author to conduct research on CV. Angkasa Baru and choose the title